High-thermal-conductivity radiation refrigeration coating material and preparation method thereof
By covering the surface hydroxylated hBN nanosheets on the surface of SiO2 hollow sphere particles and co-doped with the polymer substrate, a radiation refrigeration coating material with high thermal conductivity was prepared, and the low thermal conductivity of radiation refrigeration materials in the prior art was solved. The problem is that efficient cooling of electronic devices is achieved.
Patent Information
- Application Number
- CN202411467752.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-21
AI Technical Summary
The low thermal conductivity characteristics of existing radiation refrigeration materials are not conducive to the heat dissipation of electronic devices, and limit their application and development in the field of thermal management of electronic devices.
By covering the surface hydroxylated hBN nanosheets on the surface of SiO2 hollow sphere particles, hollow SiO2@hBN composite particles were prepared and multi-shaped co-doped with the polymer substrate to form a radiation refrigeration coating material with high thermal conductivity. Multi-layer structure improves reflective performance and thermal conductivity.
It achieves high thermal conductivity and excellent radiation refrigeration effect, improves the solar band reflectivity and infrared band emissivity, and effectively improves the cooling performance of electronic devices.
Smart Images

Figure CN119192916A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coating materials, and in particular to a high thermal conductivity radiation refrigeration coating material and a preparation method thereof. Background Art
[0002] As electronic devices become increasingly miniaturized and highly integrated, extremely high heat flux density and hot spots have become one of the important reasons restricting the further development of microelectronic devices. It is urgent to find new, low-energy and efficient cooling technologies to ensure the stable operation of electronic devices. Radiative cooling technology transfers heat to the low-temperature environment of outer space through thermal radiation to achieve the purpose of passive cooling of objects. This technology does not require any additional energy consumption, is conducive to energy conservation and carbon reduction, and has great application potential in the field of thermal management of electronic devices.
[0003] However, the materials currently used in radiation cooling generally have extremely low thermal conductivity, and the multi-layer, porous and other structures used to improve the radiation performance of the material lead to further reduction in thermal conductivity. The low thermal conductivity of radiation cooling materials is not conducive to the heat dissipation of electronic devices, which greatly affects the normal operation of electronic devices and limits the application and development of radiation cooling materials in this field. Therefore, it is particularly important to develop a radiation cooling coating material with high thermal conductivity. Summary of the invention
[0004] The purpose of the present invention is to provide a high thermal conductivity radiation cooling coating material and a preparation method thereof, so as to solve the problems existing in the above-mentioned prior art.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention: a method for preparing a high thermal conductivity radiation cooling coating material, comprising the following steps:
[0007] The surface of SiO2 hollow sphere particles with surface amino groups was coated with hBN nanosheets with surface hydroxylation to obtain hollow SiO2@hBN composite particles.
[0008] Surface hydroxylated hBN micron sheets and hollow SiO2@hBN composite particles are added to a solvent containing a dispersant and dispersed evenly to obtain a raw material solution. A polymer base solution is then added to the raw material solution, dispersed evenly and coated to obtain the high thermal conductivity radiation refrigeration coating material.
[0009] Furthermore, the preparation method of the hollow SiO2@hBN composite particles specifically comprises:
[0010] The SiO2 hollow sphere particles are added to an organic solvent solution and dispersed uniformly, the pH is adjusted to acidic to obtain a mixed solution, a silane coupling agent containing an amino group is added to the mixed solution, and the mixture is heated and stirred for reaction to obtain SiO2 hollow sphere particles with surface amino groups;
[0011] The hBN nanosheets are subjected to high temperature heating treatment in an air atmosphere to obtain surface hydroxylated hBN nanosheets;
[0012] The SiO2 hollow sphere particles with surface amino groups and the hBN nanosheets with surface hydroxy groups are added to a solvent and dispersed evenly, and then the pH is adjusted to acidic, and the reaction is stirred to obtain the hollow SiO2@hBN composite particles.
[0013] Furthermore, the particle size of the SiO2 hollow sphere particles is 0.5-5 μm; the amount ratio of the SiO2 hollow sphere particles to the organic solvent in the organic solvent solution is 2-3.5 g: 250-450 mL; the pH of the mixed solution is 5; the volume ratio of the amino-containing silane coupling agent to the mixed solution is (0.5-0.8): (60-100); the temperature of the heating and stirring reaction is 60° C. and the time is 6 hours;
[0014] The high temperature heating treatment is performed at a temperature of 1000°C and a time of 3 hours;
[0015] The mass ratio of the surface aminated SiO2 hollow sphere particles and the surface hydroxylated hBN nanosheets is (9-12):(5-6); the total amount of the surface aminated SiO2 hollow sphere particles and the surface hydroxylated hBN nanosheets and the amount of the solvent is 0.7-0.8g:100-120mL; the stirring reaction time is 4h.
[0016] Furthermore, the amount ratio of the solvent containing the dispersant, the surface hydroxylated hBN micro-sheets and the hollow SiO2@hBN composite particles is 20-55 mL: 0.72-1.92 g: 0.36-0.96 g;
[0017] The ratio of the polymer substrate to the solvent in the polymer substrate solution is 2-4.5 g:12-25 mL;
[0018] The dosage ratio of the dispersant to the solvent in the solvent containing the dispersant is 0.08-0.2 g: 20-55 mL.
[0019] Furthermore, the mass ratio of the total mass of the surface hydroxylated hBN micro-sheets and hollow SiO2@hBN composite particles to the polymer substrate is 1.08-2.88 g:2-4.5 g.
[0020] Furthermore, the method for preparing the surface hydroxylated hBN microsheets comprises the following steps:
[0021] The hBN microsheets are subjected to high temperature heating treatment in an air atmosphere to obtain surface hydroxylated hBN microsheets;
[0022] The temperature of the high temperature heating treatment is 1000° C. and the time is 3 hours.
[0023] The second technical solution of the present invention: a high thermal conductivity radiation cooling coating material prepared by the above preparation method.
[0024] The third technical solution of the present invention: an application of the above-mentioned high thermal conductivity radiation cooling coating material in the preparation of electronic devices.
[0025] The present invention discloses the following technical effects:
[0026] (1) The high thermal conductivity radiation cooling coating material prepared by the present invention has high thermal conductivity and excellent radiation cooling effect (i.e., high solar band reflectivity and infrared band emissivity), and is suitable for the field of thermal management of electronic devices.
[0027] (2) The present invention uses boron nitride microsheets (surface hydroxylated hBN microsheets) and hollow spherical particles coated with boron nitride (hollow SiO2@hBN composite particles) to co-dope the polymer substrate in multiple shapes, so that the coating material has good radiation cooling effect and high thermal conductivity. Specifically:
[0028] A layer of hBN nano-flaky particles is coated on the surface of SiO2 hollow particles, and the scattering of incident light is improved through the multi-layer structure, thereby optimizing the reflective performance of the coating material, improving the reflectivity of the coating material to sunlight, and reducing the absorption of solar radiation.
[0029] SiO2 hollow particles coated with boron nitride (hollow SiO2@hBN composite particles) and hBN micron flake particles with hydroxylation on the surface are used for multi-shape co-doping. The hollow SiO2@hBN composite particles have high reflectivity in the ultraviolet and visible light bands, and the high reflectivity of the hBN micron flake particles with hydroxylation on the surface is coupled to improve the reflectivity of the entire solar radiation band, and optimize the reflectivity of the coating material to the greatest extent. At the same time, the PVDF-HFP polymer substrate used has extremely high emissivity in the atmospheric window band, and the particle doping has a weak effect on the infrared emissivity. Therefore, the coating material prepared by the present invention has excellent reflectivity and emissivity, and can achieve a good radiation cooling effect.
[0030] The present invention coats boron nitride on the surface of SiO2 hollow particles, and due to the high thermal conductivity of the boron nitride material, the thermal conductivity of the filler is greatly improved. In addition, the multi-shape co-doping strategy adopted can form a thermal conductive network inside the coating material, which is conducive to the formation of a thermal conductive channel, thereby greatly improving the thermal conductivity of the material. The high thermal conductivity of the coating material is conducive to the heat generated by the operation of the electronic device to be transferred outward through heat conduction and heat convection, coupled with radiation cooling, to achieve efficient cooling of the electronic device. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 FTIR images of the raw material SiO2 hollow sphere particles used in Example 1 of the present invention, the surface amino-treated SiO2 hollow sphere particles prepared in Example 1, and the hollow SiO2@hBN composite particles prepared in Example 1;
[0033] Figure 2 This is a SEM image of the hollow SiO2@hBN composite particles prepared in Example 1 of the present invention;
[0034] Figure 3 This is a cross-sectional view of the high thermal conductivity radiation cooling coating material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0035] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0036] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0037] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0038] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0039] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0040] One of the technical solutions of the present invention is to provide a method for preparing a high thermal conductivity radiation cooling coating material, comprising the following steps:
[0041] (1) Preparation method of hollow SiO2@hBN composite particles:
[0042] S1. Preparation of SiO2 hollow sphere particles with surface amino modification: SiO2 hollow sphere particles are added to an organic solvent solution (deionized water and anhydrous ethanol in a volume ratio of 1:19) and ultrasonically dispersed (10 to 30 minutes) uniformly, concentrated hydrochloric acid is added dropwise while stirring to adjust the pH to 5 to obtain a mixed solution, a silane coupling agent containing an amino group is added to the mixed solution, heated and stirred for reaction, and then washed and dried to obtain SiO2 hollow sphere particles with surface amino modification;
[0043] In a specific embodiment of the present invention, the particle size of the SiO2 hollow sphere particles is 0.5-5 μm, and the shell thickness is 50-100 nm; the amount ratio of the SiO2 hollow sphere particles to the organic solvent in the organic solvent solution is 2-3.5 g: 250-450 mL; the volume ratio of the amino-containing silane coupling agent to the mixed solution is (0.5-0.8): (60-100); the temperature of the heating and stirring reaction is 60° C., and the time is 6 hours;
[0044] In a specific embodiment of the present invention, washing is performed by repeatedly washing with anhydrous ethanol and deionized water for 2 to 3 times; and drying is performed by vacuum drying at a temperature of 60 to 70°C.
[0045] S2. Preparation of surface hydroxylated hBN nanosheets: hBN nanosheets (commercially available, with a particle size of 50 to 100 nm) were subjected to high temperature heating treatment (temperature of 1000° C. for 3 h) in an air atmosphere to obtain surface hydroxylated hBN nanosheets.
[0046] S3. Preparation of hollow SiO2@hBN composite particles: Add surface amino-modified SiO2 hollow sphere particles and surface hydroxylated hBN nanosheets into deionized water and disperse them evenly by ultrasonication (10 to 30 min). Then, concentrated hydrochloric acid is added dropwise while stirring to adjust the pH to 4. After stirring for reaction, the mixture is washed and dried to obtain hollow SiO2@hBN composite particles.
[0047] In a specific embodiment of the present invention, the mass ratio of the surface aminated SiO2 hollow sphere particles and the surface hydroxylated hBN nanosheets is (9-12): (5-6); the total amount of the surface aminated SiO2 hollow sphere particles and the surface hydroxylated hBN nanosheets and the amount of deionized water is 0.7-0.8 g: 100-120 mL; the stirring reaction time is 4 hours;
[0048] In a specific embodiment of the present invention, washing is performed by repeatedly washing with anhydrous ethanol and deionized water for 2 to 3 times; and drying is performed by vacuum drying at a temperature of 60 to 70°C.
[0049] (2) Preparation method of surface hydroxylated hBN microsheets:
[0050] The hBN microsheets (commercially available, with a particle size of about 1 μm) were subjected to high temperature heating treatment (temperature of 1000° C. for 3 h) in an air atmosphere to obtain surface hydroxylated hBN microsheets.
[0051] (3) Preparation method of high thermal conductivity radiation cooling coating material (hollow SiO2@hBN / hBN-PVDF-HFP composite material):
[0052] S1. Take a polymer substrate (PVDF-HFP, weight average molecular weight M w 400,000) was dissolved in NMP by mechanical stirring at room temperature to obtain a solution of the polymer substrate.
[0053] In a specific embodiment of the present invention, the usage ratio of the polymer base and NMP is 2-4.5 g:12-25 mL.
[0054] S2. Add a dispersant to NMP and stir at room temperature for 20 to 30 minutes to obtain a solvent containing a dispersant; add the hollow SiO2@hBN composite particles prepared in step (1) and the surface hydroxylated hBN microsheets prepared in step (2) to the solvent containing a dispersant and disperse them evenly by ultrasonic dispersion (10 to 30 minutes) to obtain a raw material solution.
[0055] In a specific embodiment of the present invention, the amount ratio of the dispersant and NMP in the solvent containing the dispersant is 0.08-0.2 g: 20-55 mL; the amount ratio of the solvent containing the dispersant, the surface hydroxylated hBN microsheets and the hollow SiO2@hBN composite particles is 20-55 mL: 0.72-1.92 g: 0.36-0.96 g.
[0056] S3. The polymer substrate solution prepared in step S1 and the raw material solution prepared in step S2 are mixed, ultrasonically dispersed (30 to 60 minutes) to make them uniform, and then defoamed in a vacuum environment, and then uniformly coated and dried to obtain a high thermal conductivity radiation cooling coating material.
[0057] In a specific embodiment of the present invention, the mass ratio of the total mass of the surface hydroxylated hBN micro-sheets and hollow SiO2@hBN composite particles to the mass ratio of the polymer substrate is 1.08-2.88 g: 2-4.5 g.
[0058] In a specific embodiment of the present invention, the drying temperature is 50° C. and the drying time is 16 to 24 hours.
[0059] In a second aspect of the present invention, there is provided a high thermal conductivity radiation cooling coating material prepared by the above preparation method.
[0060] A third aspect of the present invention provides an application of the above-mentioned high thermal conductivity radiation cooling coating material in the preparation of electronic devices.
[0061] Example 1
[0062] A method for preparing a high thermal conductivity radiation cooling coating material:
[0063] (1) Preparation of hollow SiO2@hBN composite particles:
[0064] S1. Preparation of SiO2 hollow sphere particles with surface amino
[0065] 12.5 mL of deionized water and 237.5 mL of anhydrous ethanol were mixed, 2 g of SiO2 hollow sphere particles (commercially available, with a particle size of 1 to 5 μm and a shell thickness of 50 to 100 nm) were added, and concentrated hydrochloric acid was added dropwise while stirring to adjust the pH of the system to 5 to obtain a mixed solution; 2 mL of KH550 was added to the mixed solution, and the mixture was heated in a water bath at 60°C and magnetically stirred for 6 hours, followed by vacuum filtration, and the mixture was repeatedly washed with anhydrous ethanol and deionized water for 3 times, and dried in a vacuum at 60°C to obtain SiO2 hollow sphere particles with surface amino groups.
[0066] S2. Preparation of surface hydroxylated hBN nanosheets
[0067] 1 g of hBN nanosheets (commercially available, with a particle size of 50 to 100 nm) were placed in a tube furnace and heated at 1000° C. for 3 h in an air atmosphere to obtain surface hydroxylated hBN nanosheets.
[0068] S3. Preparation of hollow SiO2@hBN composite particles
[0069] Take 1.6 g of the surface amino-treated SiO2 hollow sphere particles prepared in step S1 and 0.8 g of the surface hydroxylated hBN nanosheets prepared in step S2, add them into 350 mL of deionized water, and after ultrasonic dispersion for 20 min, add concentrated hydrochloric acid dropwise while stirring to adjust the pH of the system to 4, continue stirring at room temperature for 4 h to carry out the self-assembly process, and finally perform vacuum filtration, repeatedly wash with anhydrous ethanol and deionized water for 3 times, and vacuum dry at 60°C to obtain hollow SiO2@hBN composite particles.
[0070] (2) Preparation of surface hydroxylated hBN microsheets
[0071] 1.5ghBN micron sheets (commercially available, with a particle size of about 1 μm) were placed in a tube furnace and heated at 1000°C for 3 h in an air atmosphere to obtain surface hydroxylated hBN micron sheets.
[0072] (3) Preparation of high thermal conductivity radiative cooling coating materials
[0073] S1. Take 3g PVDF-HFP (weight average molecular weight M w 400,000) was dissolved in 18 mL of NMP by mechanical stirring at room temperature to obtain a solution of the polymer substrate.
[0074] S2. Add 0.12 g of dispersant (polyvinyl pyrrolidone) to 30 mL of NMP and stir at room temperature for 30 min to obtain a NMP mixed solution. Take 1.2 g of the surface hydroxylated hBN micron sheets prepared in step (2) and 0.6 g of the hollow SiO2@hBN composite particles prepared in step (1), add them to the NMP mixed solution, and ultrasonically disperse for 20 min to obtain a raw material solution.
[0075] S3. The solution of the polymer substrate prepared in step S1 and the raw material solution prepared in step S2 are mixed, and after ultrasonic dispersion for 40 minutes, defoaming is performed in a vacuum environment, and then the mixture is evenly coated on the electronic device with a scraper, and dried at 50°C for 18 hours to obtain a high thermal conductivity radiation cooling coating material (i.e., a hollow SiO2@hBN / hBN-PVDF-HFP composite material).
[0076] The composite material prepared in this embodiment was taken to characterize radiation characteristics, and it was found that the reflectivity of the composite material prepared in this embodiment in the solar band was as high as 89.7%, and the emissivity in the infrared band was as high as 93.1%.
[0077] The thermal conductivity of the composite material prepared in this example is compared with that of the pure PVDF-HFP coating material. It is found that the thermal conductivity is from 0.146 W·m -1 ·K -1 Increased to 0.88W·m -1 ·K -1 Therefore, the composite material (coating material) prepared in this embodiment has more excellent radiation cooling characteristics and thermal conductivity, which is beneficial to the heat dissipation of electronic devices.
[0078] The preparation method of pure PVDF-HFP coating material is as follows: 3 g of PVDF-HFP is dissolved in 18 mL of NMP by mechanical stirring at room temperature, and after defoaming under vacuum, it is directly coated evenly on the electronic device with a scraper, and dried at 50°C for 18 hours to obtain pure PVDF-HFP coating material.
[0079] The FTIR images of the raw material SiO2 hollow sphere particles (SiO2), the surface amino-treated SiO2 hollow sphere particles (SiO2-KH550) prepared in this embodiment, and the hollow SiO2@hBN composite particles (SiO2@hBN) prepared in this embodiment are shown in FIG. Figure 1 .
[0080] from Figure 1 It can be seen that compared with SiO2 hollow particles, the absorption peak of SiO2-KH550 hollow particles appears at 3438cm -1 and 1635cm -1 This is caused by the vibration of -NH2. -1 and 1392cm -1 A new absorption peak appeared at 1409 cm, which corresponds to the vibration of -CH2 in KH550. The results show that KH550 is successful in the surface amino treatment of hollow sphere particles. By comparing the infrared spectrum curves of hollow particles before and after coating, it can be found that the absorption peak at 1409 cm -1 and 814cm -1 The BN characteristic peak at , indicating that the hBN coating on the surface of SiO2 hollow particles has been achieved.
[0081] The SEM image of the hollow SiO2@hBN composite particles (SiO2@hBN) prepared in this example is shown in Figure 2 .
[0082] from Figure 2 It can be seen that hBN nanosheets are successfully coated on the surface of SiO2 hollow particles.
[0083] The cross-sectional view of the high thermal conductivity radiation cooling coating material prepared in this embodiment is shown in Figure 3 .
[0084] from Figure 3 It can be seen that the particles are evenly dispersed in the polymer base material, and the hBN microsheets are dispersed between the hollow SiO2@hBN composite particles to form a heat conduction network, which is beneficial to the improvement of the thermal conductivity of the coating material.
[0085] Example 2
[0086] A method for preparing a high thermal conductivity radiation cooling coating material:
[0087] (1) Preparation of hollow SiO2@hBN composite particles:
[0088] S1. Preparation of SiO2 hollow sphere particles with surface amino
[0089] Mix 20 mL of deionized water and 380 mL of anhydrous ethanol, add 3 g of SiO2 hollow sphere particles (particle size of 1 to 5 μm, shell thickness of 50 to 100 nm), ultrasonically disperse for 30 minutes, and then drop concentrated hydrochloric acid while stirring to adjust the pH of the system to 5 to obtain a mixed solution; add 3 mL of KH550 to the mixed solution, heat in a water bath at 60°C and stir magnetically for 6 hours, then vacuum filter, wash repeatedly with anhydrous ethanol and deionized water for 3 times, and vacuum dry at 60°C to obtain SiO2 hollow sphere particles with surface amino.
[0090] S2. Preparation of surface hydroxylated hBN nanosheets
[0091] 1.5 g of hBN nanosheets (commercially available, with a particle size of 50-100 nm) were placed in a tube furnace and heated at 1000° C. for 3 h in an air atmosphere to obtain surface hydroxylated hBN nanosheets.
[0092] S3. Preparation of hollow SiO2@hBN composite particles
[0093] Take 2g of the surface amino-treated SiO2 hollow sphere particles prepared in step S1 and 1g of the surface hydroxylated hBN nanosheets prepared in step S2.1, add them to 450mL of deionized water, and ultrasonically disperse them for 30min, then add concentrated hydrochloric acid dropwise while stirring to adjust the pH of the system to 4. Continue stirring at room temperature for 4h to carry out the self-assembly process. Finally, vacuum filter and wash repeatedly with anhydrous ethanol and deionized water for 3 times, and vacuum dry at 60°C to obtain hollow SiO2@hBN composite particles.
[0094] (2) Preparation of surface hydroxylated hBN microsheets
[0095] A 2.5 ghBN micron sheet (commercially available, with a particle size of about 1 μm) was placed in a tube furnace and heated at 1000° C. for 3 h in an air atmosphere to obtain a surface hydroxylated hBN micron sheet.
[0096] (3) Preparation of high thermal conductivity radiative cooling coating materials
[0097] S1. Take 2g PVDF-HFP (weight average molecular weight M w 400,000) was dissolved in 12 mL of NMP by mechanical stirring at room temperature to obtain a solution of the polymer substrate.
[0098] S2. Add 0.18 g of dispersant (polyvinyl pyrrolidone) to 55 mL of NMP and stir at room temperature for 30 min to obtain a NMP mixed solution. Take 1.92 g of the surface hydroxylated hBN micron sheets prepared in step (2) and 0.96 g of the hollow SiO2@hBN composite particles prepared in step (1), add them to the NMP mixed solution, and ultrasonically disperse for 30 min to obtain a raw material solution.
[0099] S3. The solution of the polymer substrate prepared in step S1 and the raw material solution prepared in step S2 are mixed, and after ultrasonic dispersion for 50 minutes, defoaming is performed in a vacuum environment, and then the mixture is evenly coated on the electronic device with a scraper, and dried at 50°C for 24 hours to obtain a high thermal conductivity radiation cooling coating material (i.e., a hollow SiO2@hBN / hBN-PVDF-HFP composite material).
[0100] The composite material prepared in this embodiment was taken to characterize radiation characteristics, and it was found that the reflectivity of the composite material prepared in this embodiment in the solar band was as high as 94.9%, and the emissivity in the infrared band was as high as 91.2%.
[0101] The thermal conductivity of the composite material prepared in this example is compared with that of the pure PVDF-HFP coating material. It is found that the thermal conductivity is from 0.146 W·m -1 ·K -1 Increased to 1.32W·m -1 ·K -1 Therefore, the composite material (coating material) prepared in this embodiment has more excellent radiation cooling characteristics and thermal conductivity, which is beneficial to the heat dissipation of electronic devices.
[0102] Comparative Example 1
[0103] The same as Example 1, except that the hollow SiO2@hBN composite particles doped in the coating material are replaced with the same amount of surface hydroxylated hBN micron flakes (i.e., only surface hydroxylated hBN micron flakes are used for doping, keeping the total amount of particles unchanged), and the solar band reflectivity of the coating material is reduced from 89.7% to 83.0%.
[0104] Comparative Example 2
[0105] The same as Example 1, except that the surface hydroxylated hBN micron sheets doped in the coating material are replaced with the same amount of hollow SiO2@hBN composite particles (i.e., only hollow SiO2@hBN composite particles are used for doping, and the total amount of particles is kept unchanged), the solar band reflectivity of the coating material is reduced from 89.7% to 78.1%, and the thermal conductivity is reduced from 0.88 W·m -1 ·K -1 Reduced to 0.469W·m -1 ·K -1 .
[0106] Comparative Example 3
[0107] The same as Example 1, except that the hollow SiO2@hBN composite particles doped in the coating material are replaced with the same amount of SiO2 hollow particles, the solar band reflectivity of the coating material is reduced from 89.7% to 79.6%, and the thermal conductivity is reduced from 0.88 W·m -1 ·K -1 Reduced to 0.693W·m -1 ·K -1 .
[0108] Comparative Example 4
[0109] The same as Example 1, except that the polymer substrate (PVDF-HFP, weight average molecular weight M w 400,000) was replaced with the same amount of polymethyl methacrylate PMMA (weight average molecular weight M w 350,000), the infrared band emissivity of the coating material is reduced from 93.1% to 91.1%.
[0110] Comparative Example 5
[0111] Same as Example 1, except that the polymer substrate (PVDF-HFP) in the coating material is replaced with the same amount of polydimethylsiloxane PDMS (weight average molecular weight M w ~25,000), the emissivity of the coating material decreased from 93.1% to 91.9%.
[0112] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a high thermal conductivity radiation cooling coating material, characterized in that: The following steps are involved: The surface of SiO2 hollow sphere particles with surface amino groups was coated with hBN nanosheets with surface hydroxylation to obtain hollow SiO2@hBN composite particles. Surface hydroxylated hBN micron sheets and hollow SiO2@hBN composite particles are added to a solvent containing a dispersant and dispersed evenly to obtain a raw material solution. A polymer base solution is then added to the raw material solution, dispersed evenly and coated to obtain the high thermal conductivity radiation refrigeration coating material.
2. The preparation method according to claim 1, characterized in that: The preparation method of the hollow SiO2@hBN composite particles specifically comprises: The SiO2 hollow sphere particles are added to an organic solvent solution and dispersed uniformly, the pH is adjusted to acidic to obtain a mixed solution, a silane coupling agent containing an amino group is added to the mixed solution, and the mixture is heated and stirred for reaction to obtain SiO2 hollow sphere particles with surface amino groups; The hBN nanosheets are subjected to high temperature heating treatment in an air atmosphere to obtain surface hydroxylated hBN nanosheets; The SiO2 hollow sphere particles with surface amino groups and the hBN nanosheets with surface hydroxy groups are added to a solvent and dispersed evenly, and then the pH is adjusted to acidic, and the reaction is stirred to obtain the hollow SiO2@hBN composite particles.
3. The preparation method according to claim 2, characterized in that: The particle size of the SiO2 hollow sphere particles is 0.5-5 μm; the amount ratio of the SiO2 hollow sphere particles to the organic solvent in the organic solvent solution is 2-3.5 g: 250-450 mL; the pH of the mixed solution is 5; the volume ratio of the amino-containing silane coupling agent to the mixed solution is (0.5-0.8): (60-100); the temperature of the heating and stirring reaction is 60° C. and the time is 6 hours; The high temperature heating treatment is performed at a temperature of 1000°C and a time of 3 hours; The mass ratio of the SiO2 hollow sphere particles with surface amino groups and the hBN nanosheets with surface hydroxylation groups is (9-12):(5-6); and the stirring reaction time is 4 hours.
4. The preparation method according to claim 1, characterized in that: The usage ratio of the surface hydroxylated hBN micron sheets and the hollow SiO2@hBN composite particles is 0.72-1.92 g: 0.36-0.96 g.
5. The preparation method according to claim 1, characterized in that: The mass ratio of the total mass of the surface hydroxylated hBN micro-sheets and hollow SiO2@hBN composite particles to the mass of the polymer substrate is 1.08-2.88 g:2-4.5 g.
6. The preparation method according to claim 1, characterized in that: The method for preparing the surface hydroxylated hBN micron sheet comprises the following steps: The hBN microsheets are subjected to high temperature heating treatment in an air atmosphere to obtain surface hydroxylated hBN microsheets; The temperature of the high temperature heating treatment is 1000° C. and the time is 3 hours.
7. A high thermal conductivity radiation cooling coating material prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the high thermal conductivity radiation cooling coating material according to claim 7 in the preparation of electronic devices.
Citation Information
Patent Citations
Micro-nano lamellar boron nitride / rubber composite material and preparation method thereof
CN103319898A
Preparation methods of metal surface treatment agent containing nano boron nitride and corrosion-resistant coating
CN106010181A
Efficient heat dissipation coating for surface of aluminum alloy radiator and preparation method of efficient heat dissipation coating
CN113308160A
Efficient radiation cooling coating for surface of power distribution cabinet of power grid and preparation method of efficient radiation cooling coating
CN113943516A
Lubricating oil additive as well as preparation method and application thereof
CN114479990A
Cited By
Silica micropowder-boron nitride composite material as well as preparation method and application thereof
CN119822376A
Silicon powder-boron nitride composite material, preparation method and application thereof
CN119822376B
Hollow glass / TiO2 super-hydrophobic radiation cooling coating, method and application of hollow glass / TiO2 super-hydrophobic radiation cooling coating
CN121574622A
Radiation refrigeration material and preparation method and application thereof
CN121735269A
